Intratympanic Dexamethasone via Saturated Gelfoam for Idiopathic Sudden Sensorineural Hearing Loss. (4th December 2018) - Lundy, Larry; Karatayli Ozgursoy, Selmin; Kleindienst, Samantha
Abstract : The duration of contact time of intratympanic steroids at the round window is a variable that can potentially affect the ultimate concentration within the cochlea. By placing Gelfoam saturated with dexamethasone directly over the round window, contact time is prolonged and potentially increases the dexamethasone concentration within the cochlea. This technique is simple, readily available with standard instruments and ingredients, and easily done in the office.